2022
DOI: 10.12740/pp/onlinefirst/133919
|View full text |Cite
|
Sign up to set email alerts
|

Will MDMA-assisted psychotherapy become a breakthrough in treatment-resistant post-traumatic stress disorder? A critical narrative review.

Abstract: Zespół stresu pourazowego (Post-Traumatic Stress Disorder, PTSD) jest powszechnie występującym zaburzeniem psychicznym powstającym na skutek traumatycznych doświadczeń. Pomimo wielu dostępnych możliwości pomocy, obejmujących zarówno farmakoterapię, jak i psychoterapię, działania te niejednokrotnie nie przynoszą oczekiwanych rezultatów. W ciągu ostatnich lat przemysł farmaceutyczny nie był w stanie zaoferować nowych opartych na wielu mechanizmach działania rozwiązań, stąd uwaga części badaczy skierowała się w s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…3,4-Methylenedioxymethamphetamine, most commonly referred to as MDMA or ecstasy, is a phenylethylamine that releases a large amount of serotonin into synaptic clefts approximately 60 min after oral ingestion, causing a sense of oneness with the world, increased empathy, and heightened sensations to audiovisual stimuli [60]. The effect of this compound is multifaceted, as it not only causes a sudden increase in serotonin, but also acts directly on the α2-adrenergic, serotonin, histamine, β-adrenergic, and dopamine D1 and D2 receptors, and alters the levels of prolactin, oxytocin, cortisol, adrenocorticotropic hormone, and vasopressin [61]. The recent phase III clinical trials confirmed the safety and high efficacy of MDMA in the treatment of post-traumatic stress disorder [62].…”
Section: 4-methylenedioxymethamphetamine (Mdma Ecstasy)mentioning
confidence: 99%
“…3,4-Methylenedioxymethamphetamine, most commonly referred to as MDMA or ecstasy, is a phenylethylamine that releases a large amount of serotonin into synaptic clefts approximately 60 min after oral ingestion, causing a sense of oneness with the world, increased empathy, and heightened sensations to audiovisual stimuli [60]. The effect of this compound is multifaceted, as it not only causes a sudden increase in serotonin, but also acts directly on the α2-adrenergic, serotonin, histamine, β-adrenergic, and dopamine D1 and D2 receptors, and alters the levels of prolactin, oxytocin, cortisol, adrenocorticotropic hormone, and vasopressin [61]. The recent phase III clinical trials confirmed the safety and high efficacy of MDMA in the treatment of post-traumatic stress disorder [62].…”
Section: 4-methylenedioxymethamphetamine (Mdma Ecstasy)mentioning
confidence: 99%
“…However, that type of psychotherapy assistance is targeted exclusively at treatment-resistant patients with PTSD. The MAP approach is also intriguing from the standpoint of our paper because of the potential role of oxytocin in its effects [ 94 ]. The effectiveness of this approach is seen mainly in influencing the memory of extinction.…”
Section: Further Directionsmentioning
confidence: 99%
“…Considering that for patients with other psychiatric conditions, an estimated past-year comorbidity circulates around 57.9% [8], and what is more, in many cases, especially in a warzone or during a migration crisis, the availability of cognitive-behavioral psychotherapy might not always be present, there is a clear need for an effective, attainable, fast-acting and relatively safe medication. The history of using psychedelics, such as psylocybin, especially in a religious and magical context, dates back thousands of years ago [9], while others like MDMA were not synthesized until the first half of the 20th century [10].…”
Section: Introductionmentioning
confidence: 99%